ELECTRONIC CONDUCTION;CLASSICAL AND QUANTUM THEORY TO NANOELECTRONIC DEVICES - Xanthakis, John P. (BOCA RATON : CRC PRESS, 2020)
Electronic Conduction: Classical and Quantum Theory to Nanoelectronic Devices provides a concise, complete introduction to the fundamental principles of electronic conduction in microelectronic and nanoelectronic devices, with an emphasis on integrating the quantum aspects of conduction. The chapter coverage begins by presenting the classical theory of conduction, including introductory chapters on quantum mechanics and the solid state, then moving to a complete presentation of essential theory for understanding modern electronic devices. The author's unique approach is applicable to microscale and nanoscale device simulation, which is particularly timely given the explosion in the nanoelectronics field. Features Self-contained Gives a complete account of classical and quantum aspects of conduction in nanometer scale devices Emphasises core principles, the book can be useful to electrical engineers and material scientists, and no prior course in semiconductors is necessary Highlights the bridge to modern electronics, first presenting the physics, and then the engineering complications related to quantum behaviour Includes many clear, illustrative diagrams and chapter problem sets Gives an account of post-Silicon devices such as the GaAs MOSFET, the CNT-FET and the vacuum transistor Showcases why quantum mechanics is necessary with modern devices due to their size and corresponding electron transport properties Discusses all the issues that will enable readers to conduct their own research
OCLC-licensed vendor bibliographic record.
Keywords: Electric conductivity; Nanoelectronics; Quantum theory; SCIENCE / Physics; TECHNOLOGY / Electronics / General; TECHNOLOGY / Nanotechnology